Exploration The Multifaceted Role Of Vitamins In Epigenetic Regulation: Insights Into DNA Methylation And Histone Modification - Perkasa, Tengku Arief Buana; Puspasari, Anggelia; Priskila, Loury; Tarigan, Nadir Putra Indra; Widyawati, Dwi; Neldi, Vina (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2025)
Background: Recent research shows that vitamins actively regulate epigenetic mechanisms like DNA methylation and histone changes. Gene regulation, cellular differentiation, and disease development depend on these pathways. Aims: This review aims to synthesize current evidence on how vitamins A, B, C, D, E, and K influence epigenetic regulation, and to elucidate their potential roles in health maintenance and disease prevention. Methods: NCBI and ScienceDirect were used to search English-language literature from 2015 to 2024 for a narrative review. To capture vitamins' direct and indirect impacts on epigenetic pathways, selected peer-reviewed papers were qualitatively examined. Results: Vitamin A affects gene expression via receptor-mediated mechanisms which modify chromatin structure. B vitamins provide methyl donors for DNA methylation and histone changes. Vitamin C cofactors TET enzymes and histone demethylases, supporting active DNA demethylation and histone acetylation. The vitamin D receptor (VDR) affects DNA methyltransferases and histone-modifying enzymes, regulating gene transcription. Vitamins E and K modulate oxidative stress and histone changes to stabilize the epigenome, which may benefit cancer treatment and metabolic regulation. Conclusion: Vitamins' diverse and linked epigenetic regulatory activities are highlighted.  These micronutrients may help prevent and treat cancer, metabolic problems, and developmental anomalies by maintaining genomic integrity and influencing gene expression. Keywords: Vitamins, Epigenetics, DNA Methylation, Histone Modification, Nutritional Epigenetics, Gene Expression.